2016
DOI: 10.1007/s11255-016-1310-3
|View full text |Cite
|
Sign up to set email alerts
|

Nocturia indicates a poor health status and increases mortality in male patients with type 2 diabetes mellitus

Abstract: The presence of nocturia was associated with erectile dysfunction, systemic vascular events, higher mortality, and indicated poor health in male with type 2 diabetic mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 23 publications
3
15
0
Order By: Relevance
“…Liu et al [157] investigated the effects of T therapy on LUTS in 632 diabetic men and reported that men with the lowest T levels (2.21±0.51 ng/dL) had the highest prevalence of nocturia, and it was more likely to be severe (≥3 times/night). Francomano et al [126] examined the effects of T therapy for 5 years on LUTS in 20 obese men with TD and Met S and compared the findings in 20 matched subjects who remained untreated.…”
Section: Does Testosterone Therapy Improves Lower Urinary Tract Symptmentioning
confidence: 99%
“…Liu et al [157] investigated the effects of T therapy on LUTS in 632 diabetic men and reported that men with the lowest T levels (2.21±0.51 ng/dL) had the highest prevalence of nocturia, and it was more likely to be severe (≥3 times/night). Francomano et al [126] examined the effects of T therapy for 5 years on LUTS in 20 obese men with TD and Met S and compared the findings in 20 matched subjects who remained untreated.…”
Section: Does Testosterone Therapy Improves Lower Urinary Tract Symptmentioning
confidence: 99%
“…In patients with type 2 diabetes, depressive symptoms were positively associated with hyperglycemia (20) and poor prognoses (21). Nocturia was positively associated with diabetic retinopathy (22), erectile dysfunction (23) and mortality (24). The assessment of nocturia was easy to make in clinics.…”
Section: Introductionmentioning
confidence: 99%
“…As demonstrated by Liu et al in a study of 632 diabetic men, those men with the lowest testosterone levels (2.21±0.51 ng/dL) had the highest prevalence of nocturia, and it was more likely to be severe (≥3 times per night) (71). As expected from the previous discussion, those with severe nocturia had mortality 3 times that of men without severe hypogonadism at 3.5 years follow-up.…”
Section: Nocturiamentioning
confidence: 97%